2017
DOI: 10.4236/ojanes.2017.73005
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Gastric Tube Intubation: A Summary of Case Studies and Review of the Literature

Abstract: Study Objective Establish complications and risk factors that are associated with blind tube insertion, evaluate the validity of correct placement verification methods, establish the rationales supporting its employment by anesthesia providers, and describe various deployment facilitators described in current literature. Measurements An exhaustive literature review of the databases Medline, CINAHL, Cochrane Collaboration, Scopus, and Google Scholar was performed applying the search terms “gastric tube”, “com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…NGT misplacement or malposition occurs in 1.2% -2.4% of NGT placements where up to 60% of these incidents are in mechanically ventilated patients, and various studies demonstrating an increased risk for NGT malposition and associated complication in ventilated patients [1] NGT placement in specific and enteral feeding in the ICU setting is crucial and mandatory to all patients. It is a fundamental and routine maneuver in the ICU setting, usually performed by the nursing staff [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NGT misplacement or malposition occurs in 1.2% -2.4% of NGT placements where up to 60% of these incidents are in mechanically ventilated patients, and various studies demonstrating an increased risk for NGT malposition and associated complication in ventilated patients [1] NGT placement in specific and enteral feeding in the ICU setting is crucial and mandatory to all patients. It is a fundamental and routine maneuver in the ICU setting, usually performed by the nursing staff [14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite an intuitive expectation for a protective effect by mechanically ventilated apparatuses (because of the presence of a tube which theoretically obstructs the trachea and therefore may prevent NGT misplacement to occur in that location) the literature demonstrates mechanically ventilation as the most substantial risk factor for NGT misplacement [1] A 2011 critical review of 9931 nasogastric tube placements including 5 large scale studies, reported that all 5 studies report an increased risk of pulmonary misplacement among ventilated patients. The incidence reported was 30% -93% [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in gastroenterological procedures, endoscopy is inherently associated with higher aspiration risk due to compromised airway reflexes following local anaesthetic application and stenting of the upper oesophageal sphincter by the endoscope . Carefully considering whether an RSI and/or NGT is indicated in these case types is critical, though NGT placement is associated with its own risks including endobronchial placement; trauma to the nasopharyngeal and hypopharyngeal mucosa, including the piriform sinus and arytenoid cartilage; pneumothorax; and oesophageal perforation …”
Section: Discussionmentioning
confidence: 99%
“…Rarely, serious complications occur, including tracheal or bronchial placement and pneumothorax, esophageal perforation, intravascular placement and hemorrhage, and entanglement with other equipment including endotracheal tubes. 1 Anesthesia providers need to be cognizant of these complications in order to ensure rapid detection and correction of incorrectly placed or entangled orogastric tubes. The orogastric tube shown was blindly inserted after anesthetic induction and endotracheal intubation, and gastric fluid was suctioned.…”
mentioning
confidence: 99%